Enredo regulatorio: una mirada al reglamento de retiro de cableado aéreo desde el enfoque de calidad regulatoria - Montes Tapia, Karina (2024)
The abundant presence of overhead wires entangled in poles in Lima, many of them in a state of deterioration and some abandoned for no apparent purpose, generate both aesthetic and public safety concerns. The recent Regulation of Law 31595, approved on March 12, 2024, seeks to address this problem by establishing the necessary regulations for their removal. This regulation was submitted to the rigorous process of regulatory impact analysis, so it is expected to be a good regulatory design, with a clear strategy to ensure its effectiveness in solving this visible problem. In this article we will review compliance with the regulatory quality process in accordance with the current legal framework, as well as the results derived from its application.